Domestic Violence during the COVID-19 Pandemic: Evidences from Vietnamese Families - Phan Thị Thu Nguyệt; Muslem Daud (Universitas Serambi Mekkah, 2022)
Domestic violence has increased since the COVID-19 pandemic's early 2020 in many countries, including Vietnam. The violence sholud be solved. We examine 300 sample units, including 150 men and 150 women with wife status in the urban Vietnamese community, using the convenience sample and the norm sample. Results showed that domestic abuse by men is 32% more common than by women (22%). When they were asked about their feelings after inflicting acts of domestic violence on their spouses, the majority of violent offenders 64.7% said they felt regret and guilt. According to the poll, 4.8% of victims are women who do not want to engage in social activities because they feel helpless. They also feel weak as a result of the violence they have experienced. Then, it was a great concerns related to this domestic violence because of COVID-19 pandemic. More reasearch needed to solve these challenges. Keywords: Domestic Violence, COVID-19 Pandemic, Vietnamese Family.